Shoulder dystocia by severity in families: A nationwide population study - Svein Rasmussen; Cathrine Ebbing; Elham Baghestan; Lorentz Erland Linde (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Previous studies have established a history of shoulder dystocia as an important risk factor for shoulder dystocia, but studies on shoulder dystocia by severity are scarce. It is unknown if shoulder dystocia tends to be passed on between generations. We aimed to assess the recurrence risk of shoulder dystocia by severity in the same woman and between generations on both the maternal and paternal side. We also assessed the likelihood of a second delivery and planned cesarean section after shoulder dystocia. Material and methods This was a population‐based cohort study, using data from the Medical Birth Registry of Norway. To study recurrence in the same mother, we identified 1 091 067 pairs of first and second, second and third, and third and fourth births in the same mother. To study intergenerational recurrence, we identified an individual both as a newborn and as a mother or father in 824 323 mother‐offspring pairs and 614 663 father‐offspring pairs. We used Bayesian log‐binomial multilevel regression to calculate relative risks (RR) with 95% credible intervals. Results In subsequent deliveries in the same woman the unadjusted RR of recurrence was 7.05 (95% credible interval 6.39–7.79) and 2.99 (2.71–3.31) after adjusting for possible confounders, including current birthweight. The RRs were higher with severe shoulder dystocia as exposure or outcome. With severe shoulder dystocia as both exposure and outcome, unadjusted and adjusted RR was 20.42 (14.25–29.26) and 6.29 (4.41–8.99), respectively. Women with severe and mild shoulder dystocia and those without had subsequent delivery rates of 71.1, 68.9 and 69.0%, respectively. However, the rates of planned cesarean section in subsequent deliveries for those without shoulder dystocia, mild and severe were 1.3, 5.2 and 16.0%, respectively. On the maternal side the unadjusted inter‐generational RR of recurrence was 2.82 (2.25–3.54) and 1.41 (1.05–1.90) on the paternal side. Corresponding adjusted RRs were 1.90 (1.51–2.40) and 1.19 (0.88–1.61), respectively. Conclusions We found a strong recurrence risk of shoulder dystocia, especially severe, in subsequent deliveries in the same woman. The inter‐generational recurrence risk was higher on the maternal than paternal side. Women with a history of shoulder dystocia had more often planned cesarean section.